2017
DOI: 10.1016/j.neuroimage.2016.11.020
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative evaluation of voxel-based spatial mapping in diffusion tensor imaging

Abstract: This paper presents a comparative evaluation of methods for automated voxel-based spatial mapping in diffusion tensor imaging studies. Such methods are an essential step in computational pipelines and provide anatomically comparable measurements across a population in atlas-based studies. To better understand their strengths and weaknesses, we tested a total of eight methods for voxel-based spatial mapping in two types of diffusion tensor templates. The methods were evaluated with respect to scan-rescan reliab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 78 publications
3
20
0
Order By: Relevance
“…Skeletonized whole-brain white matter was chosen to minimize partial volume effects from surrounding gray matter or cerebrospinal fluid (CSF) and to increase reliability of diffusion tensor estimation in white matter. 41…”
Section: Introductionmentioning
confidence: 99%
“…Skeletonized whole-brain white matter was chosen to minimize partial volume effects from surrounding gray matter or cerebrospinal fluid (CSF) and to increase reliability of diffusion tensor estimation in white matter. 41…”
Section: Introductionmentioning
confidence: 99%
“…Mostly known for its involvement in self-referential cognition, consciousness, and memory [16], this network also plays a crucial role in attentional performance as its deactivation is a condition for a successful allocation of neural resources to task-positive regions [17]. Several recent studies revealed functional disturbances of the DMN in AD patients, including connectivity and deactivation impairments [18-20].…”
Section: Introductionmentioning
confidence: 99%
“…Data were analyzed using Quantitative Imaging Toolkit to examine diffusion tensor parameters in deep white matter, as defined by the Johns Hopkins University (JHU) white matter atlas [56]. The JHU regions were segmented in each scan using an automated atlas‐based approach described in the study by Cabeen et al [57], in which deformable tensor‐based registration using DTI toolkit [58] was used to align the subject data to the Illinois Institute of Technology diffusion tensor template [59], and subsequently to transform the JHU atlas regions to the subject data and compute the average of each diffusion tensor parameter with each JHU region. The native space T1‐weighted MRI images were used to measure estimated total intracranial volume (eTIV) and hippocampal (HC) volume using the FreeSurfer software [60], as described in the study by Sepehrband et al [61].…”
Section: Methodsmentioning
confidence: 99%